Physiology - Preston, Robin R.; Wilson, Thad E. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
An addition to the popular Lippincott's Illustrated Review (LIR) series, this comprehensive review of Physiology enables rapid review and assimilation of large amounts of complex information about the essentials of medical physiology. In keeping with the LIR series, LIR Physiology includes the popular features of the series: abundance of full-color, annotated illustrations; expanded outline format; chapter summaries; review questions; and Clinical Applications that link basic science to real-life clinical situations. The book can be used as a review text for a stand-alone physiology course in medical, health professions, and upper-level undergraduate programs or in conjunction with other LIR books for integrated courses. Ancillary online materials include full text, an image bank for faculty, and an interactive question bank for students--Provided by publisher.
Includes index.
Keywords: Physiological Phenomena